Pemberdayaan Masyarakat dalam Peningkatan Produksi Ikan Asap di Kelurahan Badarharjo Kecamatan Semarang Utara - Moh Solehatul Mustofa; Tutik Wijayanti; Noviani Achmad Putri; Mico Lesmana Putra; Nurul Amaliah; Bagus Darmawan (STIPAS Tahasak Danum Pambelum Keuskupan Palangkaraya, 2024)
The fish smoking business in Badarharjo Village has quite large potential to continue to grow. The smoked fish industry is carried out traditionally by the community and grows well with fresh fish as raw materials supplied from TPI in surrounding villages. Smoked fish entrepreneurs are dominated by mothers. Based on the situation analysis, the smoked fish produced was not stored properly, because most of the smoked fish had been cooked by buyers within a short time. Meanwhile, packaging is still done simply, namely using teak leaves or used newspaper as wrapping and then putting it in a plastic bag. Based on this, it is very important to hold Community Empowerment in Increasing Smoked Fish Production in Badarharjo Subdistrict Village in the form of training on storing and packaging processed Smoked Fish into Fozen Food. This community service activity was carried out to provide knowledge about the process of storing smoked fish properly and packaging smoked fish to make it attractive. The target output of this community service activity is publication in national journals with ISSN, news publication in mass media and video highlights of service activities uploaded to the YouTube channel. The training method in this activity is PRA (Participatory Rural Appraisal) which includes team formation, goal formulation, identification of target communities, collection and analysis of needs, determining problem solution priorities, preparation, implementation, mentoring, review and evaluation, then the final stage is determining needs. and new targets based on the results of evaluations that have been carried out. Activities are planned in two stages over two days. The first day was socialization on the importance of entrepreneurship and an introduction to vacuum equipment, the second day was training on making food packaging and labels as well as practicing the process of storing and packaging fish using vacuum techniques. This activity aims to ensure that people are able to increase their knowledge and skills in smoked fish entrepreneurship, have skills in using vacuum equipment, are able to carry out good fish packaging so that they can increase the added value of their products, and smoked fish entrepreneurs are able to increase their competitiveness in the market.